Improvement of text readability and recall through user guided highlighting and automatic formatting - Davin Ryo Tanada (Nanyang Technological University, 2021)
The growing need of global literacy has pushed for people all over the world to follow suit. Still, issues regarding literacy still exist, including lack of focus and understanding of the topics being given. Fortunately, these can hopefully be remedied via the use of special formatting of written text, aimed at improving the users’ attention towards the text, highlighting key information, and reducing the users’ weight from cluttered information. A simple prototype Android app has been created to fulfill the aims of this project. This app is aimed to be usable with any bits of text, in as many languages as possible, in order to reach a larger audience. The app functions by taking in user inputs, thus giving the app a text to format, namely by recoloring certain words based on word frequency. The user can request specific words to be specially highlighted as well. This app is intended as a step towards aiding readability in many pieces of writing everywhere, and to see use in fields outside of literature and learning, such as design and marketing.